2017
DOI: 10.1007/s00223-017-0339-3
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics, Bone and Mineral Metabolism

Abstract: Increasing interest in functional foods has driven discovery in the area of bioactive compounds. Prebiotics are non-digestible carbohydrate compounds that, when consumed, elicit health benefits and aid in the prevention and treatment of chronic diseases. While prebiotics have been shown to improve a number of chronic, inflammatory conditions, growing evidence exists for prebiotic effects on calcium metabolism and bone health. These novel dietary fibers have been shown to increase calcium absorption in the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(148 citation statements)
references
References 129 publications
5
106
0
4
Order By: Relevance
“…In contrast, another study reported that 8-week-old germ-free mice had reduced femoral length, cortical thickness, and BMD compared with conventionally raised mice [18]. Experimental data from mice in another study demonstrated that the modulation of the gut microbiota in germ-free mice using probiotics can increase bone mass [19]. To date, limited studies on human adults have directly evaluated the correlation between the gut microbiota and bone health.…”
Section: Gut Microbiota and Bone Massmentioning
confidence: 99%
“…In contrast, another study reported that 8-week-old germ-free mice had reduced femoral length, cortical thickness, and BMD compared with conventionally raised mice [18]. Experimental data from mice in another study demonstrated that the modulation of the gut microbiota in germ-free mice using probiotics can increase bone mass [19]. To date, limited studies on human adults have directly evaluated the correlation between the gut microbiota and bone health.…”
Section: Gut Microbiota and Bone Massmentioning
confidence: 99%
“…Other prebiotic effects that might influence productive performance of poultry species are alterations on lipid metabolism and mineral absorption [83,84]. Studies have demonstrated that prebiotic supplements have a positive effect on the mineral metabolism of Ca, P, Zn, Cu, and Fe [85][86][87][88], whose intake is influenced by factors such as the lower luminal pH that increases their solubility promotion and thus their passive absorption, changes in the intestinal mucosa and increased absorption surface area, elevated expression of Ca-binding proteins, release of bone-modulating factors, phytate degradation by probiotic bacteria enzymes, and improved overall intestinal health [89,90]. On the other hand, although no exact mechanisms have been reported for the alteration on lipid metabolism caused by prebiotics, it has been demonstrated that intestinal microbiota play a role in maintaining lipid metabolism [91], so that the increase in bacterial numbers or a change in the composition of the intestinal microbiota might be related to the lipidic alterations.…”
Section: Productive Performancementioning
confidence: 99%
“…The gastrointestinal tract microbiota pro le in uence nutraceutical e cacy in a non-blinded randomized clinical trial [8].The current literature on gut ora and OA suggest that gut microbiome-OA connection sets the stage for discovery of potentially OA of obesity involving strategic manipulation of speci c microbial species inhabiting the intestinal space [9]. Current gut ora mechanisms for improved mineral absorption and skeletal health include alterations in gut microbiota composition, production of short-chain fatty acids, altered intestinal pH, biomarker modi cation, immune system regulation, vitamin D and vitamin K [10,11].…”
Section: Introductionmentioning
confidence: 99%